Development and Evaluation of Anti-Gout Jam Formulation from Jamaican Cherry (Muntingia calabura) and Stevia (Stevia rebaudiana Bertoni): Antioxidant Activity and Uric Acid Reduction Potential - Nurjanah, Rizka; Anggraini, Yuliana Debora (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2025)
This study examines the potential of Jamaican cherry (JC) and stevia, a natural sweetener, as an anti-gout jam. It aims to evaluate the effects of JC leaf and stevia extracts on the jam’s chemical, physical, and organoleptic qualities, finding the optimal formulation and ascertaining whether feeding JC jam lowers mice’s blood uric acid levels. A complete block design with two factors was applied. The two factors were JC leaf extract (A1: 30%, A2: 50%, A3: 70%) and stevia extract (B1: 1%, B2: 2%, B3 3%). The findings indicate that, while there was no significant shift in the jam’s viscosity, sugar reduction, color, flavor, aroma, or spreadability, adding more JC leaf extract did affect its pH and moisture content. Similarly, stevia extract did not affect flavor, color, spreadability, viscosity, and sugar reduction, but it significantly impacted pH, moisture content, and aroma. The ideal jam formulation was a blend of 70% JC leaf extract (A3) and 3% stevia extract (B3), with a preference score of 4.66 (neutral), a viscosity of 387.50 cP, a pH of 4.16, a moisture content of 59.38%, and a sugar reduction of 1.85%. According to the results of the in vitro test, the JC jam successfully lowered uric acid levels to normal conditions at 4.92 mg/dL.